Complications of free-flap procedures for phalloplasty in female-to-male transgender surgery: 25-year experience a single medical center. Issue 3 (8th March 2022) - Wu, Szu-Hsien; Shen, Bing-Hwei; Perng, Cherng-Kang; Wang, Tien-Hsiang; Shih, Yu-Chung; Ma, Hsu; Wu, Ho-Yu
Abstract : Background: To present the complications of free-flap phalloplasty in three-staged female-to-male transgender surgery. Methods: This retrospective study included patients who underwent a three-staged free-flap phalloplasty for female-to-male transgender surgery between January 1988 and December 2013. Data regarding demographics, operative techniques, and complications were collected and analyzed. Results: A total of 101 patients with a mean age of 30.2 years were included. Phalloplasty with traditional free forearm tube-in-tube fasciocutaneous flap was performed in 25 (24.8%) patients, free forearm fasciocutaneous flap with vaginal mucosa for a prefabricated urethra in 30 (29.7%) patients, free radial forearm osteocutaneous flap with vaginal mucosa for a prefabricated urethra in 22 (21.8%) patients, and free fibula osteocutaneous flap with vaginal mucosa for a prefabricated urethra in 24 (23.8%) patients. Complication rates of partial flap loss, urethrocutaneous fistula, urethral stricture, and hair or stone formation were 12.9%, 49.5%, 24.8%, and 5.0%, respectively. Patients receiving fibula osteocutaneous flap phalloplasty had the lowest overall complication rate (33.3%), followed by those with radial forearm osteocutaneous flap (40.9%), forearm fasciocutaneous flap (43.3%), and forearm tube-in-tube fasciocutaneous flap (80.0%). Forearm tube-in-tube fasciocutaneous flap procedure was associated with significantly higher rates of overall complications ( p = 0.05), urethrocutaneous fistula ( p = 0.005), and hair or stone formation ( p = 0.002) compared with the other three types of procedures. Rates of all complications did not significantly differ among fibula osteocutaneous flap, radial forearm osteocutaneous flap, and forearm fasciocutaneous flap procedures. Conclusion: In free-flap phalloplasty for female-to-male transgender surgery, utilization of free fibula osteocutaneous flap with vaginal mucosa for a prefabricated urethra resulted in the lowest complication rate. Further comparisons among different procedures of phalloplasty are warranted.